Mode III interlaminar fracture of carbon/epoxy laminates using the Six-Point Edge Crack Torsion (6ECT) - Morais, A.B. de
The recently proposed Six-Point Edge Crack Torsion (6ECT) test was used to evaluate the mode III interlaminar fracture of carbon/epoxy laminates. Plate specimens with starter delaminations in 0/0, 0/90 and 0/45 interfaces were tested. Data reduction was performed with an effective crack scheme validated in a previous numerical study. The tests allowed the evaluation of fairly unambiguous initiation GIIIC values and of subsequent R-curves. Examinations of specimen cross-section showed considerable lengths of pure interlaminar propagation in specimens with starter delaminations in 0/90 and 0/45 interfaces. The latter specimens had the lowest initiation GIIIC values.